Nanocolumnar Crystalline Vanadium Oxide-Molybdenum Oxide Antireflective Smart Thin Films with Superior Nanomechanical Properties - Dey A.; Nayak M.K.; Esther A.C.M.; Pradeepkumar M.S.; Porwal D.; Gupta A.K.; Bera P.; Barshilia H.C.; Mukhopadhyay A.K.; Pandey A.K.; Khan K.; Bhattacharya M.; Kumar D.R.; Sridhara N.; Sharma A.K. (My University, 2025)
Vanadium oxide-molybdenum oxide (VO-MO) thin (21-475 nm) films were grown on quartz and silicon substrates by pulsed RF magnetron sputtering technique by altering the RF power from 100 to 600 W. Crystalline VO-MO thin films showed the mixed phases of vanadium oxides e.g., V 2 O 5, V 2 O 3 and VO 2 along with MoO 3. Reversible or smart transition was found to occur just above the room temperature i.e., at ∼45-50 °C. The VO-MO films deposited on quartz showed a gradual decrease in transmittance with increase in film thickness. But, the VO-MO films on silicon exhibited reflectance that was significantly lower than that of the substrate. Further, the effect of low temperature (i.e., 100 °C) vacuum (10 â '5 mbar) annealing on optical properties e.g., solar absorptance, transmittance and reflectance as well as the optical constants e.g., optical band gap, refractive index and extinction coefficient were studied. Sheet resistance, oxidation state and nanomechanical properties e.g., nanohardness and elastic modulus of the VO-MO thin films were also investigated in as-deposited condition as well as after the vacuum annealing treatment. Finally, the combination of the nanoindentation technique and the finite element modeling (FEM) was employed to investigate yield stress and von Mises stress distribution of the VO-MO thin films. © 2016 The Author(s).